KUALITAS AUDIT: LEVERAGE, KEAHLIAN KOMITE AUDIT, DAN CLIENT IMPORTANCE - Nastasya Aprilia Putri (2022)
Audit quality is a condition when audit activities comply with established regulations and provide confidence regarding the audited financial statements. This study aims to find out the effect of leverage, audit committee expertise and client importance on audit quality. The population in this study are non-financial sector companies that listed on the Indonesia Stock Exchange in 2020. This research uses a purposive sampling method by establishing several criteria. The selected samples are 530 companies. In this study, audit quality is measured by earning surprise benchmark, leverage is measured by debt to asset ratio, audit committee expertise is measured by comparison between the number of audit committees with accounting and finance background and the total audit committee, then client importance is measured by dividing the natural logarithm of assets a company with the natural asset logarithm of a company audited by a KAP. This study uses logistic regression analysis in testing with a significance level of 5%. The test results show that leverage has a significant negative relationship with audit quality, audit committee expertise has no significant relationship with audit quality, and client importance has a positive significant relationship with quality.